Biocatalytic production of bicyclic β-lactams with three contiguous chiral centres using engineered crotonases - Hamed, R; Gomez-Castellanos, J; Henry, L; Warhaut, S; Claridge, T; Schofield, C (Springer Nature, 2019)
There is a need to develop asymmetric routes to functionalised β-lactams, which remain the most important group of antibacterials. Here we describe biocatalytic and protein engineering studies concerning carbapenem biosynthesis enzymes, aiming to enable stereoselective production of functionalised carbapenams with three contiguous chiral centres. Structurally-guided substitutions of wildtype carboxymethylproline synthases enable tuning of their C-N and C-C bond forming capacity to produce 5-carboxymethylproline derivatives substituted at C-4 and C-6, from amino acid aldehyde and malonyl-CoA derivatives. Use of tandem enzyme incubations comprising an engineered carboxymethylproline synthase and an alkylmalonyl-CoA forming enzyme (i.e. malonyl-CoA synthetase or crotonyl-CoA carboxylase reductase) can improve stereocontrol and expand the product range. Some of the prepared 4,6-disubstituted-5-carboxymethylproline derivatives are converted to bicyclic β-lactams by carbapenam synthetase catalysis. The results illustrate the utility of tandem enzyme systems involving engineered crotonases for asymmetric bicyclic β-lactam synthesis.